If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2k + -8k + -12 + 2 = 2k + 4 Reorder the terms: -12 + 2 + 2k + -8k = 2k + 4 Combine like terms: -12 + 2 = -10 -10 + 2k + -8k = 2k + 4 Combine like terms: 2k + -8k = -6k -10 + -6k = 2k + 4 Reorder the terms: -10 + -6k = 4 + 2k Solving -10 + -6k = 4 + 2k Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-2k' to each side of the equation. -10 + -6k + -2k = 4 + 2k + -2k Combine like terms: -6k + -2k = -8k -10 + -8k = 4 + 2k + -2k Combine like terms: 2k + -2k = 0 -10 + -8k = 4 + 0 -10 + -8k = 4 Add '10' to each side of the equation. -10 + 10 + -8k = 4 + 10 Combine like terms: -10 + 10 = 0 0 + -8k = 4 + 10 -8k = 4 + 10 Combine like terms: 4 + 10 = 14 -8k = 14 Divide each side by '-8'. k = -1.75 Simplifying k = -1.75
| t-50=40 | | X^2+10x-77=0 | | d-37=39 | | 17m-48=2m-3 | | log(5a-8)=loga | | c-24=56 | | 2x^2=6-9x | | 5x+8/7+1=4x+1/3-5 | | 0=4t^2-9t+5 | | q-10=43 | | x*y=1470 | | 15y+20=5y-10 | | -7n-21-8+64n= | | (-2v^2+7v-4)-(-3v^2+9v-3)+(-2v^2-5v+3)=0 | | y=8x^6-1.2x^2 | | -10+90x+6x-10= | | k=3s+3w | | e-18=18 | | 20x-23=37 | | 5x+19=-4 | | 14+(-2x)=14 | | r-34=23 | | 10-3y+4y=12 | | 9x^2-3kx+k=0 | | b-85=8 | | h-71=22 | | 3x-12+12=-5x | | 3s^2-2s-40=0 | | x^2-40x-11=0 | | q-22=11 | | 9-22=11 | | 3x+5x-6=150 |